2015
DOI: 10.1515/bhk-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity of female children and adolescents based on step counts: meeting the recommendation and relation to BMI

Abstract: SummaryStudy aim: the aim of this study was to assess the step counts of children and adolescents with different BMIs and to present the results in relation to the step count recommendation. Material and methods: the study included data from 175 girls, aged 12-18 (45 participants from primary school, 69 participants from junior high school and 61 participants from high school). Voluntary participants were recruited from public schools in Poland.Step counts were measured using pedometers (Yamax Digi-Walker SW 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…A higher level of BMI in girls is assumed because girls are not more active than boys. Girls who do a small number of steps each day, have a higher BMI than those who do a high number of steps each day [8]. the high and low BMI of a child is influenced by the characteristics of the father's BMI and maternal BMI [21].…”
Section: A Bmi (Body Mass Index)mentioning
confidence: 99%
See 1 more Smart Citation
“…A higher level of BMI in girls is assumed because girls are not more active than boys. Girls who do a small number of steps each day, have a higher BMI than those who do a high number of steps each day [8]. the high and low BMI of a child is influenced by the characteristics of the father's BMI and maternal BMI [21].…”
Section: A Bmi (Body Mass Index)mentioning
confidence: 99%
“…Physical development includes changes in the body (such as: growth of the brain, nervous system, sensory organs, height and weight growth, etc. ), and changes in the ways individuals use their bodies (such as the development of motor skills) and sexual development), as well as changes in physical abilities (such as decreased heart function, vision and so on) [8]. For school-age and adolescent children, optimal physical growth and development is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing daily steps is easier than following an exercise regimen as a way to increase overall physical activity in adolescents (Woo, 2008). According to the 2010 World Health Organization recommendations, adolescents should spend more than 60 min daily performing moderate-to-vigorous physical activity (Kantanista et al, 2015), which is reported to be equivalent to an average of 10,000-11,700 steps/day (Tudor-Locke et al, 2011). Other studies have also 12,000 steps/day (Colley et al, 2012) and 10,000 steps/day (Kim et al, 2005;Parra Saldías et al, 2018) for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle interventions such as dietary modification and increasing physical activity (PA) levels are used in the management of obesity [ 6 ]. Most previous studies that examined the relations between BMI and PA measured BMI at a single timepoint [ 7 - 11 ], ignoring the time-varying nature of BMI. In recent times, the use of trajectories has enabled researchers to track the trends of variables over periods [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%